Use and Transmission of Vedic Geometric knowledge: What, Where and How? - Gautam, Dandapani; Sharma , Lekhnath; Panta, Dinesh Raj; Acharya , Jayanta (Academic Journal of Sukuna, 2025)
This article explores the geometric knowledge embedded in Vedic rituals, focusing on the construction of Agnikundas (fire altars) as detailed in the Vedic texts Sulba Sutras, Kundamandip Siddhi and also highlights the central place of geometry in Vedic rituals including the use of right-angled triangles, square roots, and precise measurements to construct ritual spaces. Through field observations and interviews with Sanskrit scholars and ritual practitioners, the research uncovers the informal transmission of this knowledge and its absence from modern Sanskrit curricula. A survey of 100 participants revealed limited awareness of these geometric principles. The knowledge of constructing Agnikundas is transmitted to the generations through participatory approach with the seniors means they learned through hands-on learning, and culturally responsive approach to learning geometry. The study indicates the need of curriculum reform on Sanskrit intuitions to include Vedic geometry used on rituals to bridge traditional knowledge and contemporary education. Integrating this ancient practice could enhance students' understanding of geometry while preserving cultural heritage.